Social media in health science education: an international survey - O'Sullivan, Elizabeth; Cutts, Emily; Kavikondala, Sushma; Salcedo, Alejandra; D'Souza, Karan; Hernandez-Torre, Martin; Anderson, Claire; Tiwari, Agnes; Ho, Kendall; Last, Jason (JMIR Publications, 2017)
Background: Social media is an asset that higher education students can use for an array of purposes. Studies have shown the merits of social media use in educational settings; however, its adoption in health science education has been slow, and the contributing reasons remain unclear. Objective: This multidisciplinary study aimed to examine health science students’ opinions on the use of social media in health science education and identify factors that may discourage its use. Methods: Data were collected from the Universitas 21 “Use of social media in health education” survey, distributed electronically among the health science staff and students from 8 universities in 7 countries. The 1640 student respondents were grouped as users or nonusers based on their reported frequency of social media use in their education. Results: Of the 1640 respondents, 1343 (81.89%) use social media in their education. Only 462 of the 1320 (35.00%) respondents have received specific social media training, and of those who have not, the majority (64.9%, 608/936) would like the opportunity. Users and nonusers reported the same 3 factors as the top barriers to their use of social media: uncertainty on policies, concerns about professionalism, and lack of support from the department. Nonusers reported all the barriers more frequently and almost half of nonusers reported not knowing how to incorporate social media into their learning. Among users, more than one fifth (20.5%, 50/243) of students who use social media “almost always” reported sharing clinical images without explicit permission. Conclusions: Our global, interdisciplinary study demonstrates that a significant number of students across all health science disciplines self-reported sharing clinical images inappropriately, and thus request the need for policies and training specific to social media use in health science education.